-13 - [3(x + 2) + 4 ] = 11 - [(2x - 2) + 1] hallar x en la ecuacion
Ismaproxd2108:
nmms me equivoque ._.
Respuestas
Respuesta dada por:
1
Respuesta:
-35
Explicación paso a paso:
-13 - [ 3X + 6 + 4 ] = 11 - [ 2X - 2 + 1 ]
-13 - 3X -6 -4 = 11 - 2X + 2 -1
-3X + 2X = 11 - 1 + 2+ 13 + 6 + 4
- X = 35
- 1 ( -X = 35 )
X = - 35
Respuesta dada por:
2
Respuesta:
bueno ahora si :v
Adjuntos:
![](https://es-static.z-dn.net/files/dd3/63dd9e366cbc43d05bbdfa54d7fad488.jpg)
Preguntas similares
hace 7 años
hace 7 años
hace 8 años
hace 8 años